Toxicologia reprodutiva de ratos adultos expostos ao 2,3,7,8-Tetraclorodibenzo-P-Dioxina (TCDD) in útero - Sanabria, Marciana [UNESP] (2014)
Dioxins are organic polychlorinated byproducts derived from several industrial processes whose most toxic form is 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD), which persists in the environment due to its cumulative character. Humans are prone to TCDD exposure, principally by ingesting contaminated foods and during critical periods of development, especially during intrauterine and postnatal life. It is known that exposure to TCDD promotes dysfunctions of the male genital system such as reduced weights of reproductive organs, delayed initiation of sexual maturation, diminished number of testicular spermatids, diminished serum testosterone levels, oxidative stress in the epididymis, decreased sperm concentration, alterations in motility and in sperm transit time. Considering the scarcity in the literature of works on the effects of TCDD on the reproductive health of male offspring, its action on reproductive functions and sperm quality should be confirmed and elucidated in both humans and experimental animals. Thus, we evaluated the effect transgenerational of in utero exposure to TCDD about genital system of adult male offspring, with emphasizing the epididymal functions and sperm quality. For this, pregnant rats were exposed to low doses of TCDD (0.1; 0.5 and 1.0μg), on gestational day 15 and subsequently their adult male offspring were investigated for fertility after artificial insemination in utero (AI). The hormones testosterone, follicle stimulating (FSH) and luteinizing (LH) were also measured. Intrauterine exposure to TCDD provoked, in adult male offspring, alterations in serum testosterone levels and sperm morphology, and diminution in sperm transit time in the cauda epididymis. Furthermore, there was reduction in the proportion of implants per corpus luteum after in utero artificial insemination, such that these alterations occurred under at least one of the doses tested in the three generations. Nevertheless, there was no ...